PERANCANGAN BRANDING TROWULAN MELALUI SITUS PURBAKALA SEBAGAI UPAYA PELESTARIAN WARISAN BUDAYA LOKAL - Wicaksono, Satrio Arif; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2015)
Abstract: The aim of the design was to Trowulan branding preserve local cultural heritage. Research conducted using qualitative research methods, namely by doing interviews, observation, documentation, library and study to get the data used as the supporter of the creation of the concept design of branding. The data were analyzed by using multiple stages, namely the reduction of the data, the presentation of data, and conclusions. From the analysis of the data found few keyword refers to the communication strategy of branding that will be used to achieve the target the intended audience. After analysis of the data, the found a concept or design branding keywords i.e.